Development of the Americ-Baker Cellular Mineral Thermal Insulating Materials for Buildings - W. J. D. Stone (Canadian Institute of Mining, Metallurgy and Petroleum, 1979)
Discussions with people knowledgeable in the insulating material field revealed that materials on the market would be considerably improved if there was a greater meeting of certain very desirable criteria. Such criteria include: (1) the material should not burn, even at higher temperatures; (2) at an elevated temperature, the material should not give off toxic gases or produce smoke; (3) the material should have a low energy input; and (4) vermin would find the material unattractive. Theoretical discussions led to the conclusion that an insulating material made by foaming a mineral, preferably of a platy nature, with an inorganic binding system that could be converted to a rigid structure at low temperature would likely meet all the above requirements. It was also theorized that the use of microwaves in the converting stage would be beneficial in the creation of a cellular structure by aiding the foamer through creating vacules of steam. Talc was selected as readily meeting the theoretical mineral requirement and the material of Baker Talc Limited was used as the basic filler. The early results obtained led to an agreement between Americ Mines Limited and Baker Talc Limited pertaining to commercial production in a specific geographic area. It was recognized that due to the economics of shipping, the availability of the basic filler material should be geographically widely spread. Samples of materials were requested and many received from all over North America and one from Britain. Enough work has been done to show that they respond to the basic process in a similar manner as the Baker Talc material. From the data acquired, it is considered that the process is applicable for the production of loose fill insulation, moulded insulation for pipes and structural steel, ceiling tile, batts, sheet and for incorporation into other products such as various roofing board materials. Sufficient development has been done to enable a budget to be prepared for the construction and operation of a loose fill insulation plant.